Predicting the demand for central bank digital currency: A structural analysis with survey data - Jiaqi Li (Bank of Canada, 2021)
This paper predicts households' demand for a central bank digital currency (CBDC) with different design attributes by applying a structural demand model to a unique Canadian survey dataset. CBDC and its close alternatives, cash and demand deposits, are viewed as product bundles of different attributes. I estimate households' preferences towards these attributes from how they allocate their liquid assets between cash and demand deposits. The estimated preferences are used to predict the demand for CBDC with a set of design attributes and quantify the impacts of CBDC design choices on CBDC demand. Under a baseline design for CBDC, the aggregate CBDC holdings out of households' liquid assets could range from 4 to 52%, depending on whether households would perceive CBDC to be closer to cash or deposits. I find that important design attributes include budgeting usefulness, anonymity, bundling of bank services and rate of return.
Keywords: E50; E58; 330; Central bank research; Digital currencies and fintech